Modelagem do efeito do terraceamento para o controle do escoamento superficial numa bacia rural no sul do Brasil - Werle, Larissa (2024)
Extreme weather events such as heavy rains and droughts require rapid adaptation of production systems to avoid the degradation of natural resources and maximize production potential. The definition of adaptive practices requires a deep understanding of the factors controlling the formation and propagation of surface runoff and the definition of specific practices for each location. The no-till system associated with complementary storm-runoff management practices is efficient for its control and related processes. However, there is little understanding of how the sizing and allocation of these practices can be planned, considering the interaction of controlling factors that occur specifically in each catchment. Planning conservation practices at the catchment scale using hydrological modeling and monitoring is an efficient alternative, as it allows the controlling factors that govern storm-runoff dynamics to be integrated. Therefore, the objective of the work was to understand the influence of different levels of conservation intervention (surface runoff control practices) on the hydrological behavior of the experimental catchment of the Guarda Mor River. The methodology was based on monitoring hydrological variables (rainfall and flow discharge) in the catchment outlet and the physiographic characterization of the catchment, such as the spatial variability of soils, topography, land use, and soil management. From a significant set of rainfall-runoff events, modeling (calibration and validation) of the generation and propagation of surface runoff was carried out with the LISEM model. Subsequently, the impacts of two conservation intervention scenarios were tested: retention strips plus well-managed no-till (C1) and level terraces plus well-managed no-till (C2). The conservation practices were assessed by considering the following hydrologic parameters: surface runoff volume, peak flow, and time to peak. The simulation results show that both intervention levels positively controlled the surface runoff. Intervention level C1 presented an average reduction in surface runoff volume and peak flow attenuation of 7% and 6%, respectively. Intervention level C2 presented an average decrease in surface runoff volume and peak flow attenuation of 30% and 28%, respectively. The results quantitatively demonstrate the positive impact of soil and water conservation practices on the drainage network. Catchment scale conservation planning is an efficient and promising strategy for improving conservation agriculture, also considering its importance in managing water resources and promoting environmental services.